2017
DOI: 10.3151/jact.15.381
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Hygral Analysis on Long-Term Natural Frequency of RC Buildings with Different Dimensions

Abstract: Gradual decay of natural frequency of reinforced concrete (RC) buildings is computationally investigated in view of the long-term moisture loss and associated shrinkage of concrete. The thermo-hygral analysis for RC lifetime over several decades is applied with monitoring data of existing multi-story buildings and nuclear power plants in service. The reduced natural frequency is numerically reproduced with delayed cracking near junction planes between structural members of different dimensions in multi-story b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Unfortunately, no experimental work was conducted to validate the numerical simulations. In [17], numerical simulations using a Thermo-Hygral model were performed on RC structures of dierent dimensions in order to show that the decrease of natural frequency due to early age eects is more important in structures having a small thickness. In [18] authors modeled the dynamic behavior of a 28 story building of real size kept in either endogenous or non-endogenous conditions using a FEM approach.…”
Section: State Of the Artmentioning
confidence: 99%
“…Unfortunately, no experimental work was conducted to validate the numerical simulations. In [17], numerical simulations using a Thermo-Hygral model were performed on RC structures of dierent dimensions in order to show that the decrease of natural frequency due to early age eects is more important in structures having a small thickness. In [18] authors modeled the dynamic behavior of a 28 story building of real size kept in either endogenous or non-endogenous conditions using a FEM approach.…”
Section: State Of the Artmentioning
confidence: 99%
“…However, studies by the authors have shown that the frequency of concrete structures decreases (i.e., the stiffness of the structure decreases) with the change in material properties with age and for different curing conditions [13][14][15][16]. To prevent the failure of RC buildings, any change in the mechanical properties of the structures due to changes in the material properties should be investigated and considered in design methods.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, drying shrinkage cracking of reinforced concrete (RC) has been viewed only as one of the causes of steel bar corrosion or as a problem of external aesthetics. However, several finite element analyses of full-modeled RC buildings, made possible by recent advancement in numerical techniques, indicate that shrinkage cracking probably affects the seismic performances of structures (Kurihara et al 2017;Kitazawa et al 2018). Figure 1 shows the seismic behavior of a 22-story RC wall building, analyzed in a study by some of the authors (Kitazawa et al 2018).…”
Section: Introductionmentioning
confidence: 99%